Pharmaceutical Perspectives on Direct Compression: Formulation and Evaluation of Antidiabetic Tablets - Masira Maksudali Saiyyad,; Dr. Deepak D. Sonawane,; Abdul Kalam, (Asian Journal of Pharmaceutical Research and Development, 2026)
Diabetes Mellitus is one of the chronic diseases that require lifetime treatment through drug therapy. Oral solid dosage forms such as tablets still form a bulk of the drug market due to the convenience, stability, and efficiency associated with them. There are various techniques used in tablet formulation. However, direct compression remains one of the most promising methods used for the production of antidiabetic drugs owing to its simplicity and cost-effectiveness as well as fewer processes involved in it. This paper aims at exploring some of the aspects of the direct compression of pharmaceutical products with special emphasis on antidiabetic drugs' formulations. The classification of drugs as well as the biopharmaceutical aspects of antidiabetic drugs (such as solubility and permeability according to Biopharmaceutics Classification System) is explained.Besides, powder blending, manufacturing of antidiabetic tablets, powder blend evaluation and evaluation of finished tablets as well as their quality attributes are discussed in detail. Other topics covered include recent developments in direct compression, such as use of co-processed excipients, nanotechnology and AI-based optimization. the current regulatory guidance and Quality by Design approach are emphasized.